NAL-NL1 Procedure for Fitting Nonlinear Hearing Aids: Characteristics and Comparisons with Other Procedures - Byrne, Denis; Dillon, Harvey; Ching, Teresa; Katsch, Richard; Keidser, Gitte (Journal of the American Academy of Audiology, 2001)
A new procedure for fitting nonlinear hearing aids (National Acoustic Laboratories' nonlinear fitting procedure, version 1 [NAL-NL1]) is described. The rationale is to maximize speech intelligibility while constraining loudness to be normal or less. Speech intelligibility is predicted by the Speech Intelligibility Index (SII), which has been modified to account for the reduction in performance associated with increasing degrees of hearing loss, especially at high frequencies. Prescriptions are compared for the NAL-NL1, desired sensation level [input/output], FIG6, and a threshold version of the Independent Hearing Aid Fitting Forum procedures. For an average speech input level, the NAL-NL1 prescriptions are very similar to those of the well-established NAL-Revised, Profound procedure. Compared with the other procedures, NAL-NL1 prescribes less low-frequency gain for flat and upward sloping audiograms. It prescribes less high-frequency gain for steeply sloping high-frequency hearing losses. NAL-NL1 tends to prescribe less compression than the other procedures. All procedures differ considerably from one another for some audiograms.Abbreviations: Al = Articulation Index, CR = compression ratio, CT = compression threshold; DSL[i/o] = desired sensation level [input/output], IHAFF = Independent Hearing Aid Fitting Forum, LGOB = loudness growth in 1/2-octave bands, NAL-NL1 = National Acoustic Laboratories' nonlinear fitting procedure, version 1, NAL-R = NAL Revised, NAL-RP = NAL-Revised, Profound, PLL = preferred listening level, POGO = prescription of gain and maximum output, RAB = Ricketts and Bentler, rms = root mean square, SII = Speech Intelligibility Index, WDRC = wide dynamic range compression
Keywords: Hearing aid prescription; nonlinear amplification; speech intelligibility